PENGARUH PENAMBAHAN PUPUK KANDANG SAPI DAN PUPUK SP-36 TERHADAP PERBAIKAN SIFAT KIMIA TANAH, PERTUMBUHAN DAN PRODUKSI TANAMAN SORGHUM (Sorghum bicolor L.) PADA TANAH TERCEMAR LIMBAH PADAT PABRIK KERTAS (LIME MUD) - Afaf Millatusy Syahidah; Bambang Hermiyanto (Jember University Press, 2019)
ABSTRACT Solid waste pollution of Paper manufacturer (Lime mud) can cause land degradation through decreasing soil quality due to chemical, physical and biological properties changes. The purpose of this study was to determine the effect of adding cow manure and SP-36 fertilizer to give improvement in the soil chemical properties, growth and production of Sorghum. Pot experiment was conducted using Randomized block Design (RBD) factorial with two factors, the first factor was soil conditions (polluted and non-polluted soil), the second factor was the type of fertilizer with 4 levels including control, cow manure (258 gram/pot), SP-36 fertilizer (0.64 gram/pot) and combination of cow manure (2658 gram/pot) and SP-36 fertilizer (0.64 gram/pot). The parameter of chemical properties observation included soil pH (pH meter), C -organic (Kurmis), Cation Exchange Capacity (extract of ammonium acetate 1 M ph 7), P-availability (Olsen) and Ca-exchanged (extract of ammonium acetate 1 M ph 7). The parameter of the plant growth and production included height of plant, dry weight of plant stem and leave and weight of 1,000 seeds. The research result revealed that combination of manure and SP36 fertilizer to the polluted soil could decrease soil pH from 8.31 to 8.17, Ca-exchanged decrease in amount of 49.58% compared to the control ones, and the increase of P-availability was in amount of 92.89% compared to the controlled ones. The addition of cow manure to the polluted soil could increase C-organic in amount of 222.7% and weight of 1,000 seeds increased in amount of 24.9% compared to the controlled ones. The provision of SP-36 treatment to the polluted soil could increase CEC of soil in amount of 3.25% and the height of plant increased to 9.31% compared to the control ones. Keyword: Manure, SP-36 fertilizer, Sorghum, Chemical Improvement, Lime mud ABSTRAK Pencemaran limbah padat Pabrik Kertas (Lime mud) dapat menyebabkan terjadinya degradasi lahan melalui penurunan kualitas tanah karena perubahan sifatkimia, fisika dan biologi tanah. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penambahan pupuk kandang sapi dan pupuk SP-36 terhadap perbaikan sifat kimia tanah, pertumbuhan dan produksi tanaman Sorghum pada tanah tercemar limbah padat (Lime mud). Percobaan pot dilakukan menggunakan Rancangan Acak Kelompok (RAK) faktorial dengan dua faktor, faktor pertama kondisi tanah (tanah tidak tercemar dan tanah tercemar), faktor kedua jenis pupuk dengan 4 taraf terdiri atas kontrol, pupuk kandang sapi (258 gram/pot) , pupuk SP-36 (0,64 gram/pot) dan kombinasi pupuk kandang sapi (258 gram/pot) dan pupuk SP-36(0,64 gram/pot). Parameter pengamatan sifat kimia tanah meliputi pH tanah (pH meter), C-organik (Kurmis), KTK tanah (ekstrak Amonium asetat 1 M ph 7), Ptersedia (Olsen) dan Ca-tertukar (ekstrak Amonium asetat 1 M ph 7). Parameter pertumbuhan dan produksi tanaman meliputi tinggi tanaman, berat kering brangkasan dan berat 1000 biji. Hasil penelitian menunjukkan kombinasi pupuk kandang dan pupuk SP-36 pada tanah tercemar dapat menurunkan pH tanah dari 8.31 menjadi 8.17, Ca-tertukar menurun sebesar 49,58 % dibanding kontrol, dan terjadi peningkatan P-tersedia sebesar 92.89 % dibandingkan dengan kontrol. Penambahan pupuk kandang sapi pada tanah tercemar mampu meningkatkan C-organik sebesar 222.7 % dan berat 1000 biji meningkat 24,9 % dibandingkan dengan kontrol. Pemberian pupuk SP-36 pada tanah tercemar dapat meningkatkan KTK tanah sebesar 3.25% dan tinggi tanaman meningkat 9.31 % dibanding kontrol. Kata kunci: Pupuk Kandang Sapi, Pupuk SP-36, Sorghum, Sifat Kimia Tanah, Lime mud